THE INFLUENCE OF INVESTMENT LITERACY, RETURN EXPECTATIONS, AND CAPITAL OF INVESTMENT ON GENERATION Z'S INVESTMENT INTEREST IN THE CAPITAL MARKET - Salsabila, Nisya; Azmi, Ika Nur; Astarani, Juanda (Universitas Bunda Mulia, 2024)
Background: The rise in the number of investors in the stock market may indicate a rise in interest in doing so. According to KSEI as of September 2023, the Indonesian financial sector is expected to be dominated by Generation Z. Objective: This research is to ascertain and evaluate the impact of investment literacy, return expectations, and minimum investment capital on the investment interest of Generation Z residing Pontianak city within the capital market. Research Methods: By utilizing primary data form distibution linkert-scale question among 53 respondents who meet the criteria, this study employs a quantitative approach to its analysis. The hypothesis testing used is partial correlation (t-test).Research Results: The results obtained show a positively and significantly impact by the return expectations and minimum capital on generation z’s investing interest in the capital market. Investment literacy does not show a positively and significantly impact on investment interest.Authenticity/Novelty of Research: This research can contributes to additional literature related to investment interest by Generation Z, wich is still rarely researched. It also re-evaluates the variable of investment literacy variables that still have different findings in previous studies.